Community Service Apply Technology To Support A Green Economy In The Bait Qurani Islamic Boarding School In Bogor District - Nurato, Nurato; Anah, Sri; Romahadi, Dedik; Enggar Pur nama , Rama; Arvisyah, Diar; Aditya, Bima (CV. Inara, 2024)
Bait Qurani was founded in 2008, under the leadership of Ustad Mahsum Salim. This Islamic boarding school is here to build an intelligent, Hafiz and Moral generation based on sincere intentions fi sabilillah. The results of a survey by a team of lecturers and students from Mercubuana University show that there are several problems that occur in this Islamic boarding school, such as large piles of organic and inorganic waste, the absence of a data collection system for students and a lack of knowledge about product sales. Based on the background above, the aim of holding this PKM activity is to provide learning about the importance of this waste problem which must be overcome, through several activities, where this worthless waste will become valuable, namely through technological processing using a composter, where this organic waste will be processed by fermentation to produce liquid fertilizer that can be sold. Likewise, inorganic waste can be recycled into valuable and useful items such as wallets, etc. To collect student data in Islamic boarding schools, how to sell using Smart Application digital marketing. It is hoped that this community service activity can solve problems in Islamic boarding schools, student data collection will be easier and will improve economic levels, so that the welfare of managers will increase.